Pelatihan Penulisan Soal Literasi dan Numerasi bagi Guru - Rizkianto, Ilham; Sarumaha, Yenny Anggreini; Putra, Aji Permana (Kurnia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2025)
The purpose of this community service activity was to provide training for teachers on designing AKM problems. The activities were conducted at MTsN 1 Sleman and involving teachers as participants. Those were held from October to November 2024 in three meetings. Through this community service activity, the team made serious efforts for teachers to understand AKM better and experience in devising literacy problems which were relevant to their own subjects. The training activities on designing literacy numeracy problems for teachers provide sufficient understanding and skills about the importance of numeracy integration in learning. Based on the discussion held and the presentation of problems designed, teachers’ competence in designing literacy numeracy that are contextual and relevant to the subjects being taught is growing. Teachers now have profound understanding how to connect numeracy concepts with learning material to create meaningful problems. Well-designed literacy numeracy problems not only test numeracy skills, but also train students in analyzing, evaluating and solving problems.